’Community-based’ as a Culturally Appropriate Concept of Development: a Case Study from Pangnirtung, Northwest Territories - Reimer, Gwen (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1993)
A community-based model of tourism development - premised on current participatory theories - is examined as a culturally appropriate process of economic development in an Inuit community. This analysis intersects issues of research methodology and practice. This paper concludes by raising several policy-related and academic implications of doing development and research in the north.